Early Antibiotic Exposure in Low-resource Settings Is Associated With Increased Weight in the First Two Years of Life. Issue 3 (September 2017) - Rogawski, Elizabeth T.; Platts-Mills, James A.; Seidman, Jessica C.; John, Sushil; Mahfuz, Mustafa; Ulak, Manjeswori; Shrestha, Sanjaya; Soofi, Sajid B.; Yori, Pablo Penataro; Mduma, Estomih; Svensen, Erling; Ahmed, Tahmeed; et al.
ABSTRACT: Objectives: The potential growth-promoting effects of antibiotics are not well understood among undernourished children in environments with high pathogen exposure. We aimed to assess whether early antibiotic exposure duration and class were associated with growth to 2 years of age across 8 low-resource sites in the MAL-ED birth cohort study. Methods: We followed 1954 children twice per week from birth to 2 years to record maternally reported antibiotic exposures and measure anthropometry monthly. We estimated the associations between antibiotic exposure before 6 months of age and weight-for-age and length-for-age (LAZ) z scores to 2 years. We assessed the impact of class-specific exposures and duration, and compared these results to effects of antibiotic exposures after 6 months of age. Results: Antibiotic use before 6 months of age was associated with increased weight from 6 months to 2 years, whereas associations with length were less consistent across sites and antibiotic classes. Compared to unexposed children, 2 or more courses of metronidazole, macrolides, and cephalosporins were associated with adjusted increases in weight-for-age of 0.24 (95% confidence interval (CI): 0.04, 0.43), 0.23 (95% CI: 0.05, 0.42), and 0.19 (95% CI: 0.04, 0.35) from 6 months to 2 years, respectively. Conclusions: Antibiotic use in low-resource settings was most associated with the ponderal growth of children who had multiple exposures to antibiotics with broad spectrum and anaerobic activity in early infancy. Opportunities for rational and targeted antibiotic therapy in low resource settings may also promote short-term weight gain in children, although longer-term physical growth and metabolic impacts are unknown. Abstract : Supplemental Digital Content is available in the text